Controlling Difficult Weeds in Citrus Groves - Kanissery, Ramdas; McAvoy, Camille; Zekri, Mongi (EDIS, 2019)
Citrus requires ‘weed-free’ tree rows for healthy growth and fruit production by reducing competition from the weeds. Many weed species can be managed by developing an herbicide program, depending on factors like the type of weeds, stage of weed growth, grove location, etc. However, certain weeds are tough to control and may require selective and timely herbicide applications, for instance, goatweed. When compared to other weed species, goatweed is relatively tolerant to many of the herbicides used in citrus. If not appropriately managed in its early growth stage, goatweed will spread quickly in the grove and will become a problematic weed in no time. This article is aimed to provide citrus growers some strategies to manage such problem weeds in their groves.